Improving Students’ Interest and Learning Outcomes in Producing Explanation Texts Through the Scientific Approach Using the Problem-Based Learning Model - Ghofir, Abdul (Edupedia Publisher, 2025)
Purpose – This study aims to address the low interest and learning outcomes of students in producing explanation texts at MA Nurul Muttaqin Wedi Kapas Bojonegoro. The main objective is to determine the improvement in students’ interest and learning outcomes through the Scientific Approach using the Problem-Based Learning (PBL) model during the 2024/2025 academic year. Methodology – This research employed a classroom action research (CAR) design involving 15 students of Grade XII Social Sciences. The study consisted of a pre-cycle and one cycle of intervention. Data were collected through observation and written tests. During the pre-cycle, students received explanation text material through conventional lecturing and completed a preliminary test. In Cycle 1, instructional actions were implemented using the PBL model to enhance students’ engagement and performance. Data analysis included descriptive comparison of student interest and test achievement before and after the intervention. Findings – The pre-cycle results showed that only 5 students (33%) demonstrated interest in producing explanation texts, while 10 students (67%) exhibited low interest. Learning outcomes were also low, with merely 1 student (6.66%) achieving the minimum mastery criterion (75). After implementing PBL in Cycle 1, student performance improved significantly: 8 students (54%) scored 100, while the remaining 7 students (46%) scored 80, resulting in a 100% mastery rate. Student interest also increased substantially based on observation indicators. These findings indicate that the PBL model effectively enhances both student interest and learning outcomes. Novelty – This study contributes to the field by demonstrating the effectiveness of integrating the Scientific Approach with the PBL model to improve students’ ability to produce explanation texts—an area that has received limited empirical attention in Indonesian secondary education. Significance – The findings provide practical insights for teachers, curriculum developers, and education practitioners in designing learning strategies that enhance student engagement and performance, especially in language learning and text production.